Pumpkinflowers : a soldier's story - Friedman, Matti, 1977- (Algonquin Books of Chapel Hill, 2016)
"Describes the author's harrowing experiences manning a remote Israeli outpost with a regiment of other young soldiers, during a small, unnamed war in the late 1990s that foreshadowed other unwinnable conflicts in the Middle East,"--NoveList.